HOT-Fit Evaluation of a Laboratory Management Information System in Vocational Higher Education - A. Labib Fardany Faisal; Aries Alfian Prasetyo; Akhmad Arif Kurdianto; Ahmad Mustofa (International Journal of Multidisciplinary Sciences and Arts, 2026)
The Laboratory and Workshop Information System named SIABEL at Politeknik Negeri Madura has been operational since January 2024, providing five core modules: Catalogue, Usage, Procurement, Inventory Verification, and Reporting. Despite more than one year of operation, active adoption remains at approximately 40% of institutional laboratory and workshop units. This study evaluates the factors influencing system adoption using the HOT-fit (Human, Organization, Technology–fit) framework, identifies functional and structural gaps, and proposes a phased system development plan grounded in evaluation findings. Data were collected via a structured five-point Likert-scale questionnaire administered to 119 respondents across four role groups — Students (74.8%), Laboratory Technicians (10.9%), Laboratory and Workshop Heads (8.4%), and Supervising Lecturers (5.9%) — drawn from four academic departments. The 44-item instrument was confirmed valid (r = 0.793–0.921) and reliable across all nine HOT-fit constructs (Cronbach's ? = 0.901–0.937). Descriptive analysis shows all constructs scored in the Good category (overall means 3.74–3.83), establishing that the adoption gap is not attributable to system quality failure but to three structural conditions: a configuration mismatch between the system and the Department of Health's laboratory workflows, functional gaps that reduce the net benefit perceived by Laboratory Technicians, and weak institutional governance. A 14-initiative, three-phase development plan is proposed, prioritizing a health laboratory configuration module, an automated notification engine, and a structured onboarding program as immediate interventions.